Meningkatkan Hasil Belajar IPA Pada Materi Struktur dan Fungsi Bagian Tumbuhan Melalui Metode Diskusi - Nurwahidah; Khaerul Anam (STKIP Taman Siswa Bima, 2023)
This study aims to determine the improvement of learning outcomes in Science, specifically on the topic of plant structure and function, for fourth-grade students at SDN 2 Dena through the implementation of the Discussion method. Data were collected from 17 students through two cycles of classroom action research. The results of the study showed a significant improvement in students' learning outcomes between Cycle I and Cycle II, with the class average increasing from 62.65 to 80. This improvement has reached the predetermined target. Additionally, the study revealed that the Discussion method effectively enhances the monitoring of teacher and student actions during the learning process, with the percentage of action monitoring increasing from 65% in Cycle I to 85% in Cycle II. These findings align with previous research indicating that the Discussion method can enhance students' understanding, active participation, and communication skills. The results of this study have important implications for educational practitioners in designing interactive and effective Science instruction to achieve desired learning objectives.